A reliability generalization meta-analysis of coefficient alpha and test–retest coefficient for the aging males' symptoms (AMS) scale. (1st October 2016) - Lee, Chin-Pang; Chiu, Yu-Wen; Chu, Chun-Lin; Chen, Yu; Jiang, Kun-Hao; Chen, Jiun-Liang; Chen, Ching-Yen
Abstract: Purpose : The aging males' symptoms (AMS) scale is an instrument used to determine the health-related quality of life in adult and elderly men. The purpose of this study was to synthesize internal consistency (Cronbach's alpha) and test–retest reliability for the AMS scale and its three subscales. Methods : Of the 123 studies reviewed, 12 provided alpha coefficients which were then used in the meta-analyses of internal consistency. Seven of the 12 included studies provided test–retest coefficients, and these were used in the meta-analyses of test–retest reliability. Results : The AMS scale had excellent internal consistency [α = 0.89 (95% CI 0.88–0.90)]; the mean alpha estimates across the AMS subscales ranged from 0.79 to 0.82. The AMS scale also had good test–retest reliability [ r  = 0.85 (95% CI 0.82–0.88]; the test–retest reliability coefficients of the AMS subscales ranged from 0.76 to 0.83. There was significant heterogeneity among the included studies. Conclusions : The AMS scale and the three subscales had fairly good internal consistency and test–retest reliability. Future psychometric studies of the AMS scale should report important characteristics of the participants, details of item scores, and test–retest reliability.